2014
DOI: 10.1016/j.hkjot.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Task-oriented Mirror Therapy for Upper Extremity Function in Stroke Patients: A Pilot Study

Abstract: Objective/Background To compare the effects of simple and task-oriented mirror therapies on upper extremity function in stroke patients with hemiplegia. Methods A single-subject, reversal (applied behaviour analysis) research design was used, and the study included four patients and two treatments. Treatment 1 involved simple mirror therapy that was performed using simple upper limb movements. Treatment 2 involved task-oriented mirror therapy that required each patient to perform functional movements associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 15 publications
1
36
0
3
Order By: Relevance
“…In general, the studies that used these tests showed statistically significant results, with improvement of the group that received MT, in comparison to the control group. Some studies used the Action Research Arm Test, the Jebsen-Taylor Test and the Motricity Index instruments and also verified improvements in the experimental group, compared to the control group 17,20,22,23 . Some of the researches also evaluated the sensorial function 16,18 and aspects such as prehension 25 , kynematics 18 and spasticy 16,20 , with varied instruments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, the studies that used these tests showed statistically significant results, with improvement of the group that received MT, in comparison to the control group. Some studies used the Action Research Arm Test, the Jebsen-Taylor Test and the Motricity Index instruments and also verified improvements in the experimental group, compared to the control group 17,20,22,23 . Some of the researches also evaluated the sensorial function 16,18 and aspects such as prehension 25 , kynematics 18 and spasticy 16,20 , with varied instruments.…”
Section: Discussionmentioning
confidence: 95%
“…The most widely used instruments for motor function were FMS 10,15,18,19,[22][23][24][25] , BMRS 15,19,23,24 , MFT 15,19,26 and BBT 19,20,23,25 , which assess the gross and fine motor function of the UL. In general, the studies that used these tests showed statistically significant results, with improvement of the group that received MT, in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Así lo corroboran Paik et al 30 que realizan un estudio en el cual comparan la realización de TE simple o la TE orientada a tareas y observan que esta última es más eficaz para promover la recuperación de la función de la extremidad superior en pacientes con accidentes cerebrovasculares. Asimismo, Bayón et al 31 aseguran que las terapias con orientación funcional a tareas y empleo de nuevas tecnologías facilitan una mayor recuperación funcional del miembro superior.…”
Section: Discussionunclassified
“…(Table 2). (Paik et al, 2014;Lin et al, 2014) These movements were conducted, using the unaffected side, and each movement was repeated 10 times.…”
Section: Outcome Measuresmentioning
confidence: 99%